3-D coupled CFD model of a periodic operation of a heating flue and coke ovens in a coke oven battery. (1st February 2016) - Smolka, Jacek; Slupik, Lukasz; Fic, Adam; Nowak, Andrzej J.; Kosyrczyk, Ludwik
Highlights: Effective coupling procedure between 2-D coke oven and 3-D heating flue models. Coke oven battery simulation according to periodic reversion and coking cycles. Transient thermal behavior of the heating wall. Evaluation of the heat demand in the coking process. Coupled model suitable for the coking process optimization. Abstract: This paper consists of an extensive analysis of a coupled CFD model developed to simulate a coke oven battery operation. The proposed model includes a representative heating flue and two neighboring coke oven half-chambers. The heating system fully reflects the unsteady and spatially local character of heat delivery to the walls. The model is also capable of simulating arbitrary coke oven gas and hard coal compositions. Finally, the model accounts for coal drying, as well as for the release of volatiles. The obtained results show very satisfactory agreement between the measured and computed variations of temperature of the heating flue and coke oven in both reversion and coking cycles. Those in the coke oven are rather typical, but those monitored on the heating wall are not present in the literature.